The Comprehensive Midwifery Care For Mrs “D” With Prenatal Yoga To Reduce Back Pain In Third Trimester Of Pregnant Women - Ra. Aminah Maya; Sukmawati (Jurnal Inspirasi Kesehatan, 2023)
Backgrounds: Back pain can have an impact on the mother's posture so that it can cause the mother's posture to change into lordosis and kyphosis. One of the holistic treatments that can reduce back pain is prenatal yoga. Purpose: To provide comprehensive midwifery care to Mrs. "D" with the application of prenatal yoga and conducting a literature review on the effect of prenatal yoga on reducing back pain in third trimester pregnant women. Method: The method used is a case study, the subject is a 29 weeks pregnant woman. The application of prenatal yoga is carried out 6 times, 2 times a week for 3 weeks with a duration of 30 minutes. Data collection techniques through interviews, observation, physical examination and SOAP forms. Result: Comprehensive midwifery care provides good results for the mother. The process of prenatal yoga gave significant results from a score of 6 at the beginning of doing prenatal yoga to a score of 1 at the end of doing prenatal yoga, these results are in accordance with 10 journals that have conducted literature reviews. Conclusion :The author has been able to carry out comprehensive midwifery care for Mrs "D" with prenatal yoga to reduce back pain in the third trimester of pregnant women.